Zhang Yimou’s Film on Traditional Chinese Opera - Sun , Youxin; Wechkama , Thitisak (Journal of Ecohumanism, 2024)
The incorporation of Chinese operatic cultural elements characterizes the films of Zhang Yimou. His directorial works feature a variety of traditional Chinese operas, including Beijing opera, Henan opera, Nuoxi, shadow play, and Qin opera. Zhang integrates these elements into the film scores, transforming them into cinematic music. In his narratives, Zhang assigns roles of opera performers, intersperses opera performances, and incorporates operatic music segments. Additionally, operatic elements like water sleeves and theatrical masks are woven into the costumes and props. Zhang Yimou’s films significantly enhance the Chineseness and local flavor of Chinese films, reinforce narrative strength, and amplify a distinctively Chinese aesthetic. The fusion of Zhang Yimou’s films with Chinese operatic culture provides a novel pathway for integrating Chinese film with traditional culture.